Strategi Penyutradaraan Dalam Produk Kampanye Sistem Pengelolaan Pengaduan Pelayanan Publik Nasional Layanan Aspirasi Pengaduan Online Rakyat Inspektorat Jawa Barat - Arsalan Rafi Alviandi; Alfa Taufan Latif (Jurnal Penelitian Sosial Ilmu Komunikasi, 2026)
This project was motivated by the challenge of public communication in socializing the SP4N LAPOR system at the West Java Inspectorate, which tends to be administrative in nature and therefore less appealing to audiences on digital platforms. This project aims to analyze creative strategies and implement the director’s role in translating persuasive communication concepts into the visual narrative of a Public Service Advertisement (PSA) video. The method used in this project is the Multimedia Development Life Cycle (MDLC), which consists of the stages of concept, design, material collection, production (assembly), testing, and distribution. Data were collected through observation, interviews, active participation, and literature studies. The results of the project indicate that the application of directing techniques integrating visual elements, cinematography, and dramatic rhythm was able to transform administrative messages into content that is more persuasive, engaging, and emotionally connected with the public. The conclusion of this project emphasizes that digital creative strategies play an important role in bridging the information gap between government institutions and the public in order to improve the effectiveness of public communication and institutional accountability.